Correlation Between Vestibular Disorders and Superior Semicircular Dehiscence on High-resolution Computed Tomography at Tam Anh Ho Chi Minh General Hospital - Cong Trinh TRAN; Thi Lan Huong LE; Tran Thi Thuy HANG; Nghi Hai MA; Ho Hoang PHUONG; Tran Phanchung THUY (Medeniyet Medical Journal)
Objective: Superior semicircular canal dehiscence (SSCD) is a pathologic condition within the inner ear characterized by various vestibular manifestations. Numerous studies have reported an incidence rate of SSCD ranging from 3.6% to 9% in the general population. The objective of this medical study was to evaluate the prevalence of superior SSCD and investigate its correlation with vestibular symptoms among patients who underwent high-resolution computed tomography (HRCT) scans. To the best of our knowledge, there is limited research and awareness regarding SSCD in Vietnam. In addition, the secondary aim of our investigation is to assess the prevalence of SSCD in Vietnam and compare it with findings from previous studies worldwide. Methods: This retrospective study was conducted at Tam Anh Ho Chi Minh General Hospital from March 2022 to February 2024. Medical records and HRCT scans of the patients were collected. Patients were categorized into two groups: those with and without vestibular disorders. SSCD was defined as the absence of bone overlying the superior semicircular canal facing toward the dura of the middle cranial fossa. Statistical analysis was performed to determine the correlation between vestibular symptoms and the presence of SSCD. Results: A total of 362 patients (including 151 men and 211 women) were recruited. The prevalence of SSCD was 10.2% according to the HRCT scan results. The study found that 18.33% of patients with vestibular disorders had SSCD on HRCT scans, whereas only 6.2% of patients without vestibular disorders exhibited SSCD, indicating a significant association (p-value <0.001). Conclusions: These findings highlight the importance of considering SSCD as a potential etiology in patients presenting with vestibular symptoms and emphasize the diagnostic utility of HRCT.